Does migration threaten the sustainability of European welfare states? - Peter Huber; Doris A. Oberdabernig (WWWforEurope, 2013)
We investigate the relative contributions of migrant and native households to welfare states. Using two step Oaxaca-Blinder decompositions that control for selection into benefit take-up, we are able to identify the individual variables contributing to differences in welfare receipt by native and migrant households. We find that most of the differences are explained by observable characteristics such as size of the household as well as age and education of its head and income in some countries. In contrast, significantly lower net contributions of migrant households to the state budget persist in many countries even after controlling for observable factors. The reasons for this are primarily lower tax payments of migrant households. Selective migration and sound integration policies and as well as policies avoiding marginalization of migrants in informal labor markets are therefore the most effective means to avoid fiscal burdens of migration.
Keywords: J61; J15; H53; I38; 330; Oaxaca-Blinder decomposition; EU-countries; migration; net contributions; welfare state